2022
DOI: 10.1007/s12094-022-02796-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of delays in the management of lung cancer patients in the last decade: systematic review

Abstract: Introduction Due to the importance of lung cancer early treatment because of its severity and extent worldwide a systematic literature review was conducted about the impact of delays in waiting times on the disease prognosis. Materials and Methods We conducted a systematic search of observational studies (2010-2020) including adult patients diagnosed with lung cancer and reporting healthcare timelines and their clinical consequences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
0
19
1
Order By: Relevance
“…In 2020, lung cancer resulted in approximately 18% of cancer deaths, and this illness is one of the most pervasive cancers worldwide [ 1 ]. Limited access to prompt diagnosis and therapy due to the lack of early observable symptoms has resulted in the five-year survival rate for lung cancer becoming the lowest among all cancers [ 2 , 3 ]. Typically, the disease is only discernible at phases where the cancerous cells or tissues are numerous and widespread in the body, during which chemotherapy is a routine remedial recourse to curb the malignant tumor from spreading.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, lung cancer resulted in approximately 18% of cancer deaths, and this illness is one of the most pervasive cancers worldwide [ 1 ]. Limited access to prompt diagnosis and therapy due to the lack of early observable symptoms has resulted in the five-year survival rate for lung cancer becoming the lowest among all cancers [ 2 , 3 ]. Typically, the disease is only discernible at phases where the cancerous cells or tissues are numerous and widespread in the body, during which chemotherapy is a routine remedial recourse to curb the malignant tumor from spreading.…”
Section: Introductionmentioning
confidence: 99%
“…A large variability in time-to-treatment for lung cancer has previously been reported. Some studies found that shorter time-to-treatment was associated with improved prognosis, while others found the opposite or concluded that no signi cant relationship exists between waiting times and cancer prognosis [16,17]. Such inconsistencies may be attributable to the waiting time bias, in which the most urgent patients are more likely to receive care most rapidly following diagnosis, in addition to variability in the sociodemographic or clinical characteristics of the study participants and the utilization of different cutoff values for classifying delays in treatment [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…A large variability in time-to-treatment for lung cancer has previously been reported. Some studies found that shorter time-to-treatment was associated with improved prognosis, while others found the opposite or concluded that no signi cant relationship exists between waiting times and cancer prognosis [16,17].…”
Section: Discussionmentioning
confidence: 99%